Parental Social Support as a Predictor of Student Career Adaptability - Rahmi, Alfi; Firman, Firman; Afdal, Afdal (Jurnal Educative: Journal of Educational Studies, 2023)
This study aims to describe the form of social support that students receive from their parents as a form of social support in choosing students' future careers. Facing the transition to the world of work, students face various problems entering the world of work. Social support, especially from parents, will assist students in overcoming difficulties of confusion in choosing a career, lack of information obtained, and strengthening skills in entering the world of work. This type of research is descriptive quantitative with percentage data analysis techniques. The population is Guidance and Counseling final-year students, totaling 95 people with a total sampling technique. The results of the study illustrate that 65 respondents received social support in the high category, 12 respondents were included in the very high category, 13 respondents were included in the sufficient category and 5 respondents received low social support from their parents. Of the five aspects of social support, emotional support is the highest with an average score of 20.21, appreciation support 20.47, instrument support 19.96, information support 18.98, and social network support 15.26. There needs to be an increase in social support in the aspect of social networking from parents because it will provide broad opportunities for students to enter the world of work later.